John Steinbeck in Poland. - Piotr Baracz:::Creator::::::::::::
John Steinbeck on a boar hunt in the Kraina Tysiaca Jezior region of Poland. Steinbeck's quote about the boar: 'They were running so nicely I didn't have the heart to take aim.' Original is in the safe.